A follow‐up on Acute Pain Services in Germany compared to international survey data. (30th October 2015) - Erlenwein, J.; Koschwitz, R.; Pauli‐Magnus, D.; Quintel, M.; Meißner, W.; Petzke, F.; Stamer, U.M.
Abstract: Background: After the introduction of instruments for benchmarking, certification and a national guideline for acute pain management, the aim of this study was to describe the current structure, processes and quality of German acute pain services (APS). Methods: All directors of German departments of anaesthesiology were invited to complete a postal questionnaire on structures und processes of acute pain management. The survey asked for staff, techniques and quality criteria, which enabled a comparison to previous data from 1999 and surveys from other countries. Results: Four hundred and eight (46%) questionnaires were returned. APS have increased considerably and are now available in 81% of the hospitals, mainly anaesthesia based. However, only 45% fulfilled the minimum quality criteria, such as the assignment of personnel, the organization of patient care during nights and weekends, written protocols for postoperative pain management, regular assessments and documenting pain scores. Staff resources varied considerably, but increased compared to 1999. Two daily rounds were performed in 71%, either by physicians and nurses (42%), by physicians only (25%) or by supervised nurses (31%). Most personnel assigned to the APS shared this work along with other duties. Only 53% of the hospitals had an integrated rotation for training their specialty trainees. Conclusions: The availability of APS in Germany and other countries has increased over the last decade; however, the quality of nearly half of the APS is questionable. Against the disillusioning background of recently reported unfavourable pain‐related patient outcomes, the structures, organization and quality of APS should be revisited.